Manusia dan Pendidikan Islam - Subri Subri (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2017)
Indeed, the universe and its contents created Allah is as a means of passage and by whom the facility is provided and prepared for the benefit of sentient beings as inhabitants of this nature. So that form of creation of the universe is not just created (playfully) without any function and even destination. Thus, operating the manusialha to the universe as well as possible. Because human beings are perfect beings who possess perfection. The perfection of human nature, according to Islam, it does not mean that humans are unique demands outside of his nature, but instead he is able to empower its potential both for themselves and others. And fatherly empowering potential of the course must be with knowledge and science that knowledge is acquired through education course